Novo método e modelos para estudos de fluxo de potência e de curto-circuito - Moura, Adriano Aron Freitas de (2013)
This thesis presents a new method of linear power flow linear power flow V-theta it also presents a new model of synchronous generator for power flow studies in three phase unbalanced radial distribution networks and modeling of wind synchronous generator in phase components for studies of short-circuit in radial distribution systems The results reveal that 1) For the linear power flow V-theta is possible to calculate like a linear and uncoupled form the active and reactive power flows in the system Thus the errors obtained with the linear power flow V-theta are usually smaller than the errors obtained in classical method of DC power flow and it is expected that the linear power flow V-theta can be used in many applications where the classical method of DC power flow is currently used 2) A new model is proposed, considering the synchronous generator directly connected to the power grid Another existing literature modeling considering the connection from the generator through rectifier and inverter is also used The two modeling are used to perform impact studies of synchronous generators excitation systems for distribution systems with three-phase modeling The results are obtained using the IEEE 13 bus - test system The modeling of synchronous generator in phase components under unbalanced conditions allow: a) calculate the active / reactive power injections in each phase of the machine b) simulate the synchronous generator as PQ bus-type and as PV bustype Along with these studies an unprecedented and detailed analysis of voltage unbalance including a mathematical proof is presented 3) the representation of synchronous windmill generators in phase components calculations in short-circuits of radial distribution systems get more accurate results than the traditional method of symmetrical components since values of mutual impedances of different values can be considered in the analysis of the system